The complexity and contradictory nature of beliefs in dealing with multilingualism—positionings of primary school teachers between support, ambivalence and rejection - Lange, Sarah Désirée; Pohlmann-Rother, Sanna; Plohmer, Anna; Müller, Tanja (Frontiers in Education, 2025)
The BLUME study founded by the German Research Foundation study (“Primary Teachers’ Beliefs Regarding Multilingualism”) describes the complexity and contradictions of primary school teachers’ beliefs. The aim is to empirically envision the whole range of beliefs held by primary school teachers. As part of the BLUME vignette study, qualitative, vignette-based interviews in the style of brief teaching case studies were conducted with 43 primary school teachers. In order to unveil the teachers’ beliefs, the study identified positioning statements that are precise statements independent of the situation and indicate the teachers’ beliefs. Using a basic coding for the positioning statements, in the first step of the analysis, text passages containing beliefs were identified, and a category system was developed inductively and deductively, presented in this article. The results show a high degree of variation in the beliefs of primary school teachers, ranging from strongly affirmative to strongly resistant beliefs. In addition, the teachers show ambivalence in dealing with multilingualism in class as well as in their reflections on their own positioning. The qualitative-empirical approach presented here makes it possible to visualise the theoretically assumed complexity and hierarchisation within the teachers’ belief systems.